ANALISA PENGARUH ARUS PENGELASAN TERHADAP SAMBUNGAN LAS DENGAN MENGGUNAKAN UJI TARIK DAN UJI LENGKUNG PADA ENGINE STAND SUZUKI VITARA - Nur Arief Shalihan; Danang Yugo Pratomo (Program Studi Teknik Otomotif, Politeknik Hasnur, 2019)
Welding is one way to connect solid objects by melting it through heating. There are several factors that affect welding, one of which is strong current. In the welding analysis, it is explained how good welding is, and which current is better used for engine stand welding. Test results from the laboratory are used as data to conduct a more accurate analysis. Welding is done using E6013 Electrode, RB 32, ampere variation of 60 80 100 A, and the test used is tensile test and bending or tensile test in accordance with the Suzuki Vitara engine stand which is welded. Based on laboratory analysis for the strongest results there are 80A currents with results of 395,105 MPa. For the results of welded joints, the “U” profile tensile test with the strongest results in the 100 A current with a yield of 525.676 MPa And for the results of welded joints in the “U” profile, the bending test with the strongest maximum curvature in the 100 A current with the results of 1084,733. Keywords: flow, welding, welding connection, tensile test, bending test